Remediävalisierung II: Zur Programmatik der Europäischen Regionalpolitik - von Wedel, Joachim (Raumforschung und Raumordnung | Spatial Research and Planning, 2010)
Contemporary European regional policy can be understood as a set of supplementary processes of ‘remedievalisation’ which, as to the relationship between EU member states and the EU itself, have been taking place for decades. The present phenomenon of remedievalisation is apparent in a dual counter-activity to a process that has in the last centuries constituted the modern European state. Pre-modern structures become visible first through an administrative supplement of the borderline by a border region, which is subsequently institutionalised as an area with inhabitants sharing a common and border-transcending mentality.